Discovery and development of novel anti-fungal peptides against foodspoiling fungi - Muhialdin B.J.; Algboory H.L.; Mohammed N.K.; Kadum H.; Hussin A.S.M.; Saari N.; Hassan Z. (Bentham Science Publishers, 2024)
Indexed by Scopus/ERA